Blessed Kuriakose Elias Chavara - Mundadan, A Mathias (Journal of Dharma, 2008)
A. Mathias Mundadan, Blessed Kuriakose Elias Chavara, Bangalore: Dharmaram Publications, 2008, pages: xx + 525, ISBN: 978-81-89958-16-9.